ERCC6L2‐associated inherited bone marrow failure syndrome. Issue 3 (6th April 2018) - Shabanova, Iren; Cohen, Elisa; Cada, Michaela; Vincent, Ajoy; Cohn, Ronald D.; Dror, Yigal
Abstract: Background: ERCC6L2‐ associated disorder has recently been described and only five patients were reported so far. The described phenotype included bone marrow, cerebral, and craniofacial abnormalities. The aim of this study was to further define the genetic and phenotypic spectrum of the disorder by summarizing the five published cases and an additional case that we identified through whole‐exome sequencing performed at the University of Toronto. Methods: Clinical data was extracted from the Canadian Inherited Marrow Failure Registry. Whole exome sequencing was performed to identify causative mutations. Results: All six cases had homozygous truncating mutations either at or upstream of the helicase domain of ERCC6L2 . All patients displayed bone marrow failure, learning or developmental delay and microcephaly. Our patient was unique in displaying features of cerebellar disease, including ataxia and dysmetria as well as an interval deterioration of the corpus callosum and generalized volume loss on MRI. Another unique feature of our patient was retinal dystrophy with macular involvement. Along with one other patient, our patient displayed craniofacial abnormalities by presenting with low‐set prominent ears, a pointed prominent chin, and deep‐set eyes. Leukemia is common among patients with inherited bone marrow failure, but thus far, none of the patients have developed this complication. Conclusions: ERCC6L2‐ associated disorder is a multisystem disorder. The phenotype spectrum includes bone marrow failure, cerebral, and craniofacial abnormalities, as well as cerebellar and retinal abnormalities. Abstract : ERCC6L2‐associated disorder has recently been described and only five patients were reported so far. The described phenotype included bone marrow failure, cerebral and craniofacial abnormalities. In this study, we further defined the genetic and phenotypic spectrum of the disorder by summarizing the published cases and an additional case that we identified through whole exome sequencing. Our patient was unique in displaying features of cerebellar disease including ataxia and dysmetria, as well as retinal dystrophy with macular involvement.